Urine Stability Studies for Novel Biomarkers of Acute Kidney Injury - Parikh, Chirag R. (2013)
BACKGROUND: The study of novel urinary biomarkers of acute kidney injury has expanded exponentially. Effective interpretation of data and meaningful comparisons between studies require awareness of factors that can adversely affect measurement. We examined how variations in short-term storage and processing might affect measurement of urine biomarkers. STUDY DESIGN: Cross-sectional, prospective. SETTING & PARTICIPANTS: Hospitalized patients from two sites: Yale New Haven Hospital (n= 52) and University of California, San Francisco Medical Center (n=36) PREDICTORS: We tested the impact of 3 urine processing conditions on these biomarkers: a) centrifugation and storage at 4°C for 48 hours before freezing at −80°C, b) centrifugation and storage at 25°C for 48 hours before freezing at −80°C, and c) uncentrifuged samples immediately frozen at −80°C. OUTCOMES: Urine concentration of five biomarkers: neutrophil gelatinase-associated lipocalin (NGAL), interleukin 18 (IL-18), kidney injury molecule 1 (KIM-1), liver-type fatty acid–binding protein (L-FABP) and cystatin C MEASUREMENTS: We measured urine biomarkers by an established ELISA method. Biomarker values were log-transformed, and agreement with a reference standard of immediate centrifugation and storage at −80°C was compared using concordance correlation coefficients (CCCs). RESULTS: Neither storing samples at 4°C for 48 hours nor centrifugation had a significant effect on measured levels, with CCCs above 0.9 for all biomarkers tested. For samples stored at 25°C for 48 hours, excellent CCC values (>0.9) were also noted between the test sample and the reference standard for NGAL, cystatin C, L-FABP and KIM-1. However, the CCC for IL-18 between samples stored at 25°C for 48 hours and the reference standard was 0.81 (95% CI, 0.66–0.96). LIMITATIONS: No comparisons to fresh “unfrozen” samples, no evaluation of the effect of protease inhibitors. CONCLUSIONS: All candidate markers tested using the specified assays showed high stability with both short-term storage at 4°C and without centrifugation prior to freezing. For optimal fidelity, urine for IL-18 measurement should not be stored at 25°C before long-term storage or analysis.